Mapping Spiritual Leadership in Today's Organizations: Bibliometrics Analysis 2017-2021 - Sugiarto Sutomo; Charles Javlean (Journal of Leadership in Organizations, 2022)
Introduction/Main Objectives: Leadership research tries to find strategies and ways of good leaders in managing organizations throughout history. With the many studies conducted, various theories of leadership were born. Spiritual Leadership is a synthesis of previous leadership, namely ethics, authenticity, stewardship and other theories. SL seeks to fully pay attention to the dimensions in humans so that individuals experience fullness in the organization. Research reveals that SL has fostered intrinsic value in individuals, resolved problems in organizations well and promoted a sustainable workplace. Background Problems: With a variety of studies related to SL, we try to map the number of journals each year, then see what keywords are correlated with SL, and find influential SL authors. Novelty: This study will look at the latest research themes between 2017-2021 and be assisted by Bibliometric analysis. Research Methods: The search was carried out in the Scopus database, on November 8, 2021. In the search terms in all titles, abstracts, and keywords, the word “spiritual leadership” was written. The filter used is the document year range from 2017 to 2021. Then the results of the scopus analysis are mapped using VosViewer. Finding/Results: The results show an average of 36 articles publish each year. The three countries that produce the most writing are America, China, and Indonesia. Authors like Fry, Usman, Ali, and Yang most frequently cited by other authors. Network analysis and density visualization identify keywords related to SL: workplace spirituality, work engagement, spiritual well-being, organizational commitment, employee performance, job satisfaction and organizational citizenship behaviour. Conclusion: SL research can be developed more broadly on the scope of themes that appear little, such as vision, job satisfaction, employee performance, organizational citizenship behavior, and work engagement. Second, SL research whose scope does not yet exist, such as Education, organizational culture and religion.